IMPLEMENTATION OF STUNTING POLICY IN BANDUNG - Miswan, Miswan (Journal of Research and Development on Public Policy, 2024)
Governments must deal with stunting from local, regional, to national levels. Bandung district is one of the areas that is very committed to overcoming and reducing stunting. The aim of this study is to explain how policy implementation is carried out from the perspective of the rules, the parties involved in the process, the policy enforcement organization, and the environmental analysis that affects the process. The focus of this research is to look from the bottom up how stunting management policies are implemented in Bandung and how society and organizational groups play a role. Qualitative descriptive methods with informant sources, triangulation of data, and data analysis are used in this study. The main focus of this research is the ability to match data with sampling techniques. The results of this study are based on an ideal policy scenario in which stunting prevention efforts in the district of Bandung follow the rules and decisions of the council. The target group of this policy is the community that is the target of the stunting prevention program. Executive groups, mainly government groups, but also psychiatric community groups, community organizations, and other related organizations. During the implementation of stunting control policies, social and economic elements of society are related to environmental factors. Stunting and low-income socio-economic conditions are closely linked to malnutrition. Considered successful, the management policy for the district focuses on various aspects so that it can be implemented properly, including in terms of policy, parties and organizations involved, and environmental factors.